TIPOLOGI MUSHAF KUNO NUSANTARA DI BRUNEI DARUSSALAM - Ahmad Jaeni; Muhammad Musadad (SUHUF, 2018)
This article presents the results of the study of Archipelago Mushaf in the collection of Brunei State Archives which so far have not been carried out specifically. This study is important to be done as the complement to the previous study being conducted by Annabel Teh Gallop in photographing the distribution of ancient manuscripts in Southeast Asia. The study conducted by Annabel has been able to map Southeast Asian manuscripts into several typologies based on the results of codicological studies. However, the study does not include the collection of Brunei State Archives which has a large collection of ancient manuscripts. Through a codicological and textual approaches, this study is expected to be able to explain the typology of ancient manuscripts existed in the collection of Brunei State Archives. The result of the study shows that the ancient manuscripts of the collection of Brunei State Archives have typologies which can be strongly identified as having the original characteristics from Java and Patani, Southern Thailand, two centers of copying productive ancient manuscripts in Southeast Asia. This fact also confirms that most of the archipelago’s ancient manuscripts have migrated from the area where they were copied to other places. Kata kunci: Ancient mushaf typology, Brunei State Archives, Archipelago manuscripts.